Geriatric Psychiatry: Substance Abuse and Aging - David Bienenfeld (Association of American Medical Colleges, 2012)
Abstract This resource is one of several specialty modules to supplement clinical experience in geriatric psychiatry. It focuses on substance abuse and aging. This resource includes a PowerPoint presentation with audio narrative, accompanied by handout, reference list, and self-assessment quiz. At our institution, this module has been implemented for about a year at the time of submission. In a parallel implementation, the instructor has delivered this presentation, along with the presentations on personality disorders and sleep, to fellows in geriatric medicine once a year for 3 years. Ratings from learners have been 3.6 to 3.8 (out of 4) for content and importance, but there has been no quiz or other means to measure educational impact on learners.